2022
DOI: 10.1016/j.jaad.2021.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of COVID-19 in patients with autoimmune blistering skin diseases: A nationwide study

Abstract: The incidence and severity of COVID-19 among patients with autoimmune bullous skin diseases (AIBD) have not been characterized in large populations. [1][2][3] We assessed the severity and mortality of COVID-19 in patients with AIBD, with a special interest in a potential risk factor related to previous treatment with rituximab.This study was conducted from February 2020 to June 2020 in 49 dermatology departments located in 12 administrative regions of France. Possible (suggestive clinical symptoms and contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…However, most patients were able to mount an efficient immunological response to vaccine, while the highest rate of failed seroconversion was registered among patients under systemic corticosteroids or B-cell depleting therapies ( 24 ). In fact, rituximab and prednisone or prednisolone doses greater than 10 mg/die were also associated with higher risk of COVID-19 and hospitalization in patients with autoimmune or rheumatic diseases ( 25 , 26 ), thus underlining the fundamental role of humoral response against SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients were able to mount an efficient immunological response to vaccine, while the highest rate of failed seroconversion was registered among patients under systemic corticosteroids or B-cell depleting therapies ( 24 ). In fact, rituximab and prednisone or prednisolone doses greater than 10 mg/die were also associated with higher risk of COVID-19 and hospitalization in patients with autoimmune or rheumatic diseases ( 25 , 26 ), thus underlining the fundamental role of humoral response against SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients with infectious pneumonia adverse events was higher than in other cohorts ( 11 , 28 ). The latter might have been increased by the COVID-19 pandemic that occurred in 2019; in this regard, a study in France previously reported that patients with AIBD receiving RTX had a 5-fold higher incidence of COVID-19 infection than patients who did not receive RTX during the first COVID-19 wave ( 45 ). Patients with AIBD with COVID-19 also demonstrated a 5.9-fold higher risk of dying ( 45 ), but no patient in this series had fatal issues.…”
Section: Discussionmentioning
confidence: 99%
“…The latter might have been increased by the COVID-19 pandemic that occurred in 2019; in this regard, a study in France previously reported that patients with AIBD receiving RTX had a 5-fold higher incidence of COVID-19 infection than patients who did not receive RTX during the first COVID-19 wave ( 45 ). Patients with AIBD with COVID-19 also demonstrated a 5.9-fold higher risk of dying ( 45 ), but no patient in this series had fatal issues. Finally, the incidences of infectious adverse events and pneumonia were lower than those reported in a study that explored their incidence according to age in a series of patients with auto-immune diseases receiving RTX ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged B-cell depletion, B-cell–T-cell crosstalk, and neutropenia are considered the possible mechanisms of increased susceptibility of COVID-19 infection following Rituximab infusion [ 53 ]. In a recent study, Joly P and colleagues [ 54 ] reported a more than 5-fold higher risk of COVID-19 infection in patients with AIBD who received Rituximab compared with those who did not. Similarly, in the Swedish, Spelman et al [ 55 ] conducted research on 476 COVID-19 cases who had formerly developed multiple sclerosis, and found Rituximab in confirmed COVID-19 patients was associated with 2.95 times the odds of hospitalization relative to other combined therapies.…”
Section: Rituximab or Not For Pemphigus Patients?mentioning
confidence: 99%